Effect of Class F Fly Ash on Strength Properties of Concrete - Anjeza Alaj; Visar Krelani; Tatsuya Numao (Salehan Institute of Higher Education, 2023)
Reducing the amount of CO2 emissions in the environment is one of the priorities of the EPA and other environmental agencies. A way to reduce CO2 emissions is by using fly ash in the concrete industry. Aside from environmental benefits, fly ash has numerous quality advantages; some of the positive effects were recognized earlier; however, in this research, the objective is to replace cement with a different percentage of class F fly ash with a low CaO content to produce sustainable concrete. Laboratory tests were performed to examine the rational percentage of cement replaced by class F fly ash in ordinary concrete C–25/30 and high-performance concrete C–50/60. In total, twelve different mix designs were prepared to examine consistency, setting time, shrinkage, and compressive strength in different periods of curing for more than 600 days. Using recycled material in new buildings still has some obstacles, but the future of construction must be green, so this research indicates that the objective of producing ordinary and high-performance concrete was achieved by replacing 30% of cement with class F fly ash. Doi: 10.28991/CEJ-2023-09-09-011 Full Text: PDF